El derecho al dominio frente a la regularización e incorporación al patrimonio municipal de los bienes mostrencos por el Gobierno Autónomo Descentralizado del cantón Guaranda. - Guaquipana Patín Freddy Paúl (2025)
The present investigative work will be framed on the theme of the right to ownership versus the regularization and incorporation into the municipal assets of the mostrenco assets by the Decentralized Autonomous Government of the Guaranda canton. Taking into account that the right to ownership, which is also called property, is the real right in a tangible thing, to enjoy and dispose of it, in accordance with the provisions of the laws and respecting the rights of others, whether individual or social. Property separate from the enjoyment of the thing is called mere or bare property a definition taken from the current Civil Code. It must be considered that property is inviolable, the State protects it and guarantees its use and use and our legislation determines that it can be acquired and transferred by any legitimate title, and no one can be deprived of their property for reasons of public utility or interest. social, prior to the payment of fair and equitable compensation. The Decentralized Autonomous Government of the Guaranda Canton, in its substitutive ordinance for the assets of Mostrencos, makes a misinterpretation and within its analysis changes, at the convenience of said entity, the legal regulations established in the Constitution and the Civil Code, and issues a resolution without that the legitimacy of this legal act be determined for the declaration as a public good of a good owned by the State. KEYWORDS: derecho dominio, mostrenco, bienes, ciudadanía.